2019
DOI: 10.1155/2019/4867904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MRgFUS Treatment on Musculoskeletal Pain: Comparison between Bone Metastasis and Chronic Knee/Lumbar Osteoarthritis

Abstract: Local bone denervation by magnetic resonance-guided focused ultrasound (MRgFUS) is a promising tool for alleviation of pain in patients with painful bone metastasis (BM). Considering the underlying mechanism of pain alleviation, MRgFUS might be effective for various bone and joint diseases associated with local tenderness. This study was conducted to clarify the therapeutic effect of focused ultrasound in patients with various painful bone and joint diseases that are associated with local tenderness. Ten patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Only five studies (N = 102) reported data on patient quality of life before and after MRgFUS treatment. Three studies (N = 58) utilized the Brief Pain Inventory Quality of Life (BPI QoL) questionnaire [50] with a mean baseline and 3-month follow-up scores of 36.2 and 28.5, respectively [13,17,22]. The pooled mean difference was − 8.5 (95% CI − 14.6; − 2.4).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Only five studies (N = 102) reported data on patient quality of life before and after MRgFUS treatment. Three studies (N = 58) utilized the Brief Pain Inventory Quality of Life (BPI QoL) questionnaire [50] with a mean baseline and 3-month follow-up scores of 36.2 and 28.5, respectively [13,17,22]. The pooled mean difference was − 8.5 (95% CI − 14.6; − 2.4).…”
Section: Quality Of Lifementioning
confidence: 99%
“…In recent years, an innovative ablation technique known as MRI-guided focused ultrasound surgery (MRgFUS) has been developed for treatment of low back pain, based on earlier successes in treating patients with pain derived from other bone and joint diseases [6]. Trials targeting lumbar facet joints have demonstrated that MRgFUS can be a safe and effective noninvasive method for treatment of facet joint pathology [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance image-guided focused ultrasound (MRgFUS) treatment enables accurate targeting and noninvasive real-time monitoring of temperature at the treatment site [12,13]. In recent years, the potential of palliative therapy for various pain conditions of bone and joint diseases has been demonstrated by accurately and reliably producing local bone denervation utilizing these crucial advantages of this system [14][15][16][17]. In a previous preliminary study, we confirmed the feasibility of this treatment targeted to the tibial plateau for painful knee OA and reported the early pain-relieving effects on chronic knee pain, although the long-lasting effects of pain alleviation and improvement of physical function remain unclear [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous preliminary study, we confirmed the feasibility of this treatment targeted to the tibial plateau for painful knee OA and reported the early pain-relieving effects on chronic knee pain, although the long-lasting effects of pain alleviation and improvement of physical function remain unclear [16]. In addition, a tendency that severe tenderness of medial knee joints was likely to be more reduced in patients who responded to the treatment than in patients who did not respond to the treatment was reported by evaluation of pressure pain thresholds (PPTs) using a handheld algometer [17]. PPTs are validated, reliable, and widely used as an additional objective method for assessing pain sensitization, involving the quantification of a patient's response to a standardized pressure stimulation of nociceptors in patients with knee OA [5,18,19].…”
Section: Introductionmentioning
confidence: 99%